Career development and systems theory : connecting theory and practice (4th edition) - Patton, Wendy, 1957-; McMahon, Mary, 1955- (Career development series, 2021)
"This fourth edition of the book represents a milestone in the history of the Systems Theory Framework of career development that attests to its continuing influence and contemporary relevance. It emphasises changes in career development theory, practice, and research since its first edition in 1999. At that time, the publication of the STF was described by reviewers as a "groundbreaking departure from traditional counseling texts", a "landmark work leading to the convergence of career development theories", and as a "rare book that not only illuminates a field of study but also advances it". Subsequent commentary attests to the strength of the metatheoretical contribution of the STF and its facilitation of links between theory, research, and practice. This book introduces systems theory and the STF, and comprehensively overviews traditional and contemporary career theory and analyses it through the metatheoretical lens of the STF. It then describes applications of the STF by applying systems thinking, systems mapping and experiential learning. Finally, the contributions and future directions of the STF are highlighted. This book provides a record of almost 30 years of contribution of the STF to career theory, research, and practice"--